Representation of knowledge structure in literary text - Yafyasova, Elvira (The Lingua Spectrum, 2025)
This article examines the representation of knowledge structures in literary texts from the perspective of cognitive stylistics. In recent years, this area of research has attracted increasing attention, as it allows for a detailed study of linguistic means and the identification of the mechanisms of text perception and interpretation based on cognitive processes occurring in the reader’s mind. In this context, a number of important questions arise that require in-depth analysis. In our article, we will consider: how a literary text reflects the structuring and categorization of knowledge, and how various cognitive formats – images, representations, schemas, and concepts – organize the information contained in the text. Secondly, we will explore which specific cognitive mechanisms are activated in the reader’s mind during the perception of the text, and how they influence its understanding and interpretation. The third objective is to investigate the influence of the author’s and reader’s conceptospheres on perception: how the coincidence or divergence of their conceptual structures determines the perception of a literary work. Finally, we will consider how cognitive categories such as “old” and “new” knowledge affect the structure and perception of the text, contributing to the dynamics of understanding and the formation of semantic layers. Addressing these issues will enable a deeper understanding of the interconnection between cognitive processes and the analysis of literary texts, as well as how knowledge and perception function within the context of a literary work.